Dense geophysical observations reveal a triggered, concurrent multi-fault rupture at the Mendocino Triple Junction - William L. Yeck; David R. Shelly; Kathryn Z. Materna; Dara E. Goldberg; Paul S. Earle (Communications Earth & Environment, 2023)
Concurrent rupture across two distinct faults at the Mendocino triple junction, California in 2021 demonstrates a level of complexity commonly only associated with larger earthquakes, as identified by a dense seismological and geodetic network